Structural characterization and anti-oxidation activity evaluation of pectin from Lonicera japonica Thunb. - Qi, Xiaodan; Yu, Yang; Wang, Xinyi; Xu, Jialei; Wang, Xiang; Feng, Zhangkai; Zhou, Yifa; Xiao, Hongxing; Sun, Lin (Frontiers in Nutrition, 2022)
Pectins are nutrient components of plants and are widely used in the food industry. In this study, one major pectin fraction (WLJP-A0.2b) with Mw of 40.6 kDa was purified from flower buds of Lonicera japonica. The structural feature and antioxidant activity of it was investigated. Monosaccharide composition, FT-IR, enzymatic hydrolysis and NMR analysis indicated that WLJP-A0.2b consisted of rhamnogalacturonan I (RG-I), rhamnogalacturonan II (RG-II) and homogalacturonan (HG) domains, with mass ratio of 0.4:1.0:2.1. The RG-I domain contained highly branched α-L-1,5-arabinan, β-D-1,4-galactan and AG-II side chains. The HG domain was released in the form of un-esterified and partly methyl-esterified and/or acetyl-esterified oligogalacturonides with degree of polymerization 1-8 after degradation by endo-polygalacturonanase. Radical scavenging assays indicated that WLJP-A0.2b exhibited antioxidant activity through the synergistic effects of different pectin domains. Oligogalacturonides, especially de-esterified oligogalacturonides, showed better antioxidant activities than RG-II and RG-I domains. Moreover, de-esterified oligogalacturonides remarkably reduced H2O2-induced reactive oxygen species production in HEK-293T cells. These results provide useful information for screening of natural antioxidants from Lonicera japonica and application of pectin in functional food field.